Effects of climate changes to wetland water resources and community adaption in Lake Chad basin Nigeria - Dogo, Alhaji Ngare (2020)
The purpose of the research was to determine the effects of climate change on wetlandwater resources. The survey has captured the research questions, objectives, types of datacollected, procedure and analysis. Data from meteorology station that covers the period of thirtyyears from 1980-2010 was used. The objective of this study was to assess the evidences of climatechange in the Lake Chad basin Borno state, measure the climate change effects on the seasonalvariations, investigate and assess the local adaptation measures undertaken by communities to theeffects of climate change on wetlands and identify the significant differences between adaptationapproaches and respondent?s gender, age and academic qualifications. Random samplingtechnique was conducted to select 252 respondents as 20% of the sample from a population of 1277.Descriptive statistics of percentages, bar charts were used to investigate and assessedthe local adaptation measures undertaken by communities to the effects of climate change onwetland water resources. Trend analysis of time series technique was use to assess the evidences ofclimate change in the study area. For the analysis of trend by season minimum and maximumtemperatures, rainfall, solar radiation, evaporation and relative humidity, theMann-Kendall test, a nonparametric method was used and has shown gradual increase and decreasein most of the seasonal values recorded. A chi-square test of association statistics wasperformed to examine the relationship between climate change and seasonal variation. Therelation between climate change and seasonal variation was significant (12, N=252)=63.761, p=0.000. Climate change does have effect on seasonal variation. The survey results alsoindicated that dredging of water bodies around the community for the storage of water was one ofthe major approaches and was largely practiced by 38.9% of the respondents in the studyarea to cope with the challenges, while, findings further reveal that 29.0% of therespondents practice digging of dams for the storage of water as another form of mitigationmeasures. Further advance statistics of Kruskal-Wallis test, Kendall?s tau-b test and ANOVAtests were all use to identify significant difference between respondents? gender, age and qualifications to adaptation approaches in the study area. The Kruskal-Wallis teststatistic showed that there was statistically significant difference in the adaptation approachesbetween the male and female gender at different stages, (1, 252) =114.959, p=0.00, witha mean rank adaptation score of 104.94 and 228.41 for general adaptive measures undertaken by thecommunities, 104.80 and 229.09 for local mitigation measures against climate change,105.50 and 225.75 for local coping measures against the effects of drying up of wetlands. Kendall?s tau-b correlation coefficients statistic ?b is 0.574 and that is statistically significant (p=0.000). Similarly, there was statistically significant differencebetween groups in relation to gender, age and qualification on general adaptive measuresundertaken by the communities and local coping measures against the effects of drying up ofwetlands by one-way ANOVA statistic (F (4, 247),=468.928, p=0.000). In conclusion, the main finding is that the existence of climate change and itssignificant effects on seasonal variation is observed. The implication of the findings revealedthat dredging of water bodies around and digging of dams for the storage of water are necessary aswell as sex, age and qualification of respondents as part of adaptation to curtail the situation ifnot the impacts will be unbearable in thenear future.